Relationship between organizational climate, job stress and job performance officer at State Education Department - Suandi, Turiman; Ismail, Ismi Arif; Othman, Zulfadli (Australian International Academic Centre, 2014)
This research aims at finding out the relationship between Organizational Climate, job stress and job performance among State Education Department (JPN) officers. The focus of the research is to determeane the job performance of state education department officers, level of job stress among the officers, level of connection between organizational climate with job stress of State Education Department officers, looking at the difference in level of performance according to demographic factors and looking at the influence of organizational climate and job stress towards job performance . Research findings pertaining level of job performance showed that 75.8% of the respondents are at a high level, 23.7% respondents are at a moderate level while 0.5% respondents are at a low level. For organizational climate, findings show that 79.0% respondents are in the moderate level, 1.6 % respondents are at a high level and 19.4% respondents are at a low level. Findings on overall level of job stress found that as many as 92.5% respondents are at a normal job stress. Only about 7.5% respondents are at a moderate level of job stress. There is not even one respondent who are facing a high level of job stress. In terms of the relationship between independent variables (organizational climate, job stress) and dependent variable (job performance), the research findings show that there is a moderate level of positive relationship which is quite significant between organizational climate and job performance of the State Education Department officers at α = 0.01 (p < 0.01; r = 0.396).